2020
DOI: 10.5014/ajot.2020.74s1-po5719
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Animal-Assisted Therapy (AAT) on Active Participation in Therapy Sessions: A Descriptive Case Series Study

Abstract: Date Presented 03/27/20 This case series examined differences in participation in OT sessions involving AAT versus no AAT. Nine children with neurological conditions completed three similar activities, once with and once without AAT. Repetitions and length of engagement were recorded for each activity. No consistent differences between the conditions were recorded, perhaps because the integration of a dog added a dynamic component, affecting how activities were completed. Primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Likewise, Binfet and Passmore (2016) found that students who attended an eight-week AAI course reported an increase in overall satisfaction and feelings of relaxation. These findings are consistent with the positive feedback received at universities which have implemented structured therapy dog programmes (e.g., Bell, 2013;Herlache-Pretzer et al, 2020).…”
Section: Introductionsupporting
confidence: 85%
“…Likewise, Binfet and Passmore (2016) found that students who attended an eight-week AAI course reported an increase in overall satisfaction and feelings of relaxation. These findings are consistent with the positive feedback received at universities which have implemented structured therapy dog programmes (e.g., Bell, 2013;Herlache-Pretzer et al, 2020).…”
Section: Introductionsupporting
confidence: 85%